The Predictive Value of Tumor Volume and Its Change on Short-Term Outcome for Esophageal Squamous Cell Carcinoma Treated With Radiotherapy or Chemoradiotherapy - Liang, Shuai; Li, Chengming; Gao, Zhenhua; Shang, Dongping; Yu, Jinming; Meng, Xue (Frontiers in Oncology, 2021)
Objectives: To investigate the tumor volume and its change on short-term outcome in esophageal squamous cell carcinoma (ESCC) patients underwent definitive radiotherapy or chemoradiotherapy. Methods and Materials: All data were retrospectively collected from 418 ESCC patients who received radiotherapy or chemoradiotherapy at our institution between 2015 and 2019. Short-term outcome using the treatment response evaluation was assessed according to the RECIST 1.1. The tumor volume change rate (TVCR) was defined as follows: TVCR = {1 – [gross tumor volume (GTV) at shrinking irradiation field planning)] / (GTV at the initial treatment planning)} ×100%. Chi square test was used to compare the clinic characteristics in different TVCR groups, and the difference between initial GTV (GTVi) and shrinking GTV (GTVs) was compared using Wilcoxon’s sign rank test. Logistic regression analysis and spearman correlation was performed. Results: There was a significant decrease in GTVi compared to GTVs (P<0.001). In univariate analysis, age, cT-stage, TNM stage, treatment modality, GTVi and TVCR were associated with short-term outcome (all P<0.05). In multivariate analysis, gender and TVCR were statistically significant (P=0.010, <0.001) with short-term outcome. And the combined predictive value of gender and TVCR is exceeded of TVCR (AUC, 0.876 vs 0.855). Conclusions: TVCR could serve to forecast short-term outcome of radiotherapy or chemoradiotherapy in ESCC. It was of great significance to guide the individualized treatment of ESCC